Bridging Crystal Engineering and Drug Discovery by Utilizing Intermolecular Interactions and Molecular Shapes in Crystals. Issue 47 (19th August 2019) - Spackman, Peter R.; Yu, Li‐Juan; Morton, Craig J.; Parker, Michael W.; Bond, Charles S.; Spackman, Mark A.; Jayatilaka, Dylan; Thomas, Sajesh P.
Abstract: Most structure‐based drug discovery methods utilize crystal structures of receptor proteins. Crystal engineering, on the other hand, utilizes the wealth of chemical information inherent in small‐molecule crystal structures in the Cambridge Structural Database (CSD). We show that the interaction surfaces and shapes of molecules in experimentally determined small‐molecule crystal structures can serve as effective tools in drug discovery. Our description of the shape and interaction propensities of molecules in their crystal structures can be used to screen them for specific binding compatibility with protein targets, as demonstrated through the high‐throughput profiling of around 138 000 small‐molecule structures in the CSD and a series of drug–protein crystal structures. Electron‐density‐based intermolecular boundary surfaces in small‐molecule crystal structures and in target‐protein pockets are utilized to identify potential ligand molecules from the CSD based on 3D shape and intermolecular interaction matching. Abstract : Crystal clear : Highly efficient profiling of intermolecular interactions and molecular shape in crystal structures led to a new drug‐discovery approach that combines small‐molecule crystallography and protein crystallography to identify potential ligand molecules from the Cambridge Structural Database.